2002
DOI: 10.1046/j.1365-294x.2002.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and geographic distribution of secondary endosymbiotic bacteria in natural populations of the pea aphid,Acyrthosiphon pisum

Abstract: In addition to the essential intracellular symbiotic bacterium Buchnera, several facultative endosymbiotic bacteria called collectively secondary symbionts (S-symbionts) have been identified from the pea aphid Acyrthosiphon pisum. We conducted an extensive and systematic survey of S-symbionts in Japanese local populations of A. pisum using a specific PCR detection technique. Five S-symbionts of A. pisum, PASS, PAUS, PABS, Rickettsia and Spiroplasma, and two facultative endosymbionts universally found in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
303
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(330 citation statements)
references
References 32 publications
20
303
6
1
Order By: Relevance
“…In Japan, pea aphids Acyrthosiphon pisum mainly feed on vetch and clover, and many aphid clones produce more progeny on vetch than on clover. Notably, Regiella infection was detected from aphids on clover at significantly higher frequencies than on vetch [6]. Similar associations between Regiella infection and clover infestation have been identified in pea aphid populations worldwide [7 -9].…”
Section: Introductionsupporting
confidence: 64%
“…In Japan, pea aphids Acyrthosiphon pisum mainly feed on vetch and clover, and many aphid clones produce more progeny on vetch than on clover. Notably, Regiella infection was detected from aphids on clover at significantly higher frequencies than on vetch [6]. Similar associations between Regiella infection and clover infestation have been identified in pea aphid populations worldwide [7 -9].…”
Section: Introductionsupporting
confidence: 64%
“…Our results are the first to suggest probable fitness costs of SS infection of aphids in the absence of parasitism, providing insight into the unanswered question of why uninfected lineages occur at high frequencies in field populations worldwide (Sandström et al 2001;Tsuchida et al 2002;Simon et al 2003;Oliver et al 2006). Given the evidence presented here that Hamiltonella-infected aphids increase rapidly in frequency in the presence of parasitism, one would predict that Hamiltonella would be fixed or much more prevalent in natural populations where A. ervi is a common and important natural enemy (Angalet & Fuester 1977).…”
Section: Discussionmentioning
confidence: 72%
“…Serratia symbiotica was previously called PASS or R-type, H. defensa was called PABS or T-type and Regiella insecticola was called PAUS or U-type (Chen & Purcell 1997;Darby et al 2001;Sandström et al 2001;Tsuchida et al 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pea aphid, A. pisum, consists of a series of host-adapted populations that are specialized on different host plant species or genera [47][48][49]. These host-adapted populations tend to carry different species of secondary symbionts, suggesting that the symbionts might play an active role in host use and specialization on certain plant species, although these differences are not fixed between populations [32,[50][51][52][53]. Manipulation experiments have shown that the effects of the secondary symbionts on host use are complex and vary with aphid and/or symbiont genotype [54 -56].…”
Section: Are Heritable Endosymbionts Affecting Important Ecological Tmentioning
confidence: 99%